Pemahaman Calistung Pada Usia 4-6 Tahun Degan Konsep Media Go Green - Nufus, Ajijah Sadiah; Utami, Fitria Budi; Lestari, Maya (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
Teachers have the freedom to choose various open tools so that learning can be tailored to the learning needs and interests of students (Kemendikbudristek, 2022). Understanding concepts will be more optimal in learning because children do not only focus on the results but understand the learning process and children will understand a learning concept thereby forming children's competence in learning (Nufus & Pertiwi, 2021). Just like learning calistung, data shows that the level of calistung, especially in reading and writing, is still low (Data, 2015). Teachers can use various media to optimize teaching and learning activities (Nufus, 2021), not only teachers but parents can also apply various media in an activity to support children's growth and development (Ismail, 2006). In the era of technology, teachers can easily get media that supports learning. Conventional media that is made by themselves from used materials with the concept of going green has a plus point and introduces children to how to protect the earth. This research uses descriptive qualitative research. The place of research is PAUD Aisyiyah Baitul Athfaal. This research was conducted from 12-30 June 2023, and involved 50 teachers and parents. Researchers collect data using observation, interviews and documentation. Data analysis consists of data reduction, data presentation, and conclusions. Researchers provide an understanding of the growth and development of children aged 4-6 years which is integrated into calistung abilities, the results are that of the 50 research subjects the majority do not know child growth and development according to age, looking at children so that teachers and parents do not understand the concept of calistung in children aged 4-6 years . Parents choose to buy book packages for calistung according to age and teachers rely on existing book packages for calistung learning media, parents cannot make their own media using existing or used materials because they think it is troublesome and time consuming. The next step is direct practice in making media for learning calistung using used media with the concept of going green, enthusiastic teachers and parents in the process of making media using materials from used cardboard, glue, various shapes and colors of used bottle caps, cardboard and rubber bands.